Analisis Puisi “Pada Suatu Hari Nanti” Karya Sapardi Djoko Damono Dengan Pendekatan Struktural - Ayu Natasya; Dila Putri (LPPM Politeknik Pratama, 2023)
The study of structuralism of poetry is a study of poetry that emphasizes the study of the building elements of the poem itself. In this case, a poem is considered as a unified whole. Therefore, the study of poetry with the theory of structuralism is an assessment that does not involve the poet's background and other factors that influence the creation of the poem. In the study of the poem